2011 IEEE International Conference on Rehabilitation Robotics 2011
DOI: 10.1109/icorr.2011.5975374
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reaching direction on visuomotor adaptation: An explorative study

Abstract: Robotics is increasingly used in rehabilitation therapy of the hemiparetic arm after stroke. Several studies performed adaptation experiments to gain more insight in the underlying learning processes. In these studies adaptation during reaching movements in different directions is assessed. No information about influence of direction on the amount of learning to these separate directions is present. In this paper we assessed the effect of reaching direction on visuomotor learning. Forty healthy subjects perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…From the description of the experiment it could be derived that most studies provided summary feedback. Only one study focused on the effect of providing summary versus faded feedback [31] and found similar results for the summary and the faded training group. Visual Different types of augmented feedback were used solely or combined, see table 2.3.…”
Section: Effect Of the Interventionmentioning
confidence: 93%
See 4 more Smart Citations
“…From the description of the experiment it could be derived that most studies provided summary feedback. Only one study focused on the effect of providing summary versus faded feedback [31] and found similar results for the summary and the faded training group. Visual Different types of augmented feedback were used solely or combined, see table 2.3.…”
Section: Effect Of the Interventionmentioning
confidence: 93%
“…Four studies were non-randomized controlled studies (level of evidence of IV) [30][31][32][33]. Nine studies had a pre-post treatment measurement design (level of evidence of VI) [22,[34][35][36][37][38][39][40][41].…”
Section: Level Of Evidencementioning
confidence: 99%
See 3 more Smart Citations